Study on antibacterial activity (Escherichia coli) of porous ceramic fixed with silver nanoparticles - Le , Anh Quoc; Dang , Van Phu; Nguyen , Ngoc Duy; Vo , Thi Kim Lang; Nguyen , Thị Kim Lan; Nguyen , Quoc Hien; Nguyen , Quoc Hien (Nuclear Science and Technology, 2013)
Silver nanoparticles fixed in porous ceramic (AgNPs/PC) with the silver content of about 200- 250 mg/kg was prepared by impregnating porous ceramic (PC) in colloidal silver nanoparticles solution with particles size of 10 - 15 nm. Results of antibacterial activity of in vitro test for E. coli indicated that AgNPs/PC has high antibacterial efficiency of about 92% compared to 0.6% of PC. Flow test was carried out with water of an initial inoculated E. coli contamination of about 106 CFU/100ml, at the flow rate of 5 L/h. Results showed that the contamination of E. coli in filtrated water passed through AgNPs/PC (up to 500 litters) was less than 1 CFU/100ml, it is satisfactory to TCVN 6096-2004 for bottled drinking water, in comparison with 2.5x104 CFU/100ml for bare porous ceramic (only up to 40 litters). Moreover, the contents of silver released from AgNPs/PC into filtrated water samples were less than 10 μg/L, it is far below the WHO guideline of 100 μg/L silver for drinking water. Thus, AgNPs/PC candle with the silver content of 200- 250 mg/kg, the specific surface area of 1.51 m2/g and the average pore size of 48.2 Å has highly antimicrobial effect that can be applied for point-of-use drinking water treatment.